2010
DOI: 10.1590/s1516-35982010000600017
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho, qualidade dos ovos e balanço de nitrogênio de poedeiras comerciais alimentadas com rações contendo diferentes níveis de proteína bruta e lisina

Abstract: Recebido em 21/11/2008 Performance, egg quality and nitrogen balance of commercial laying hens fed diets with different levels of crude protein and lysine ABSTRACT -The experiment was carried out to evaluate the effects of diets with different levels of crude protein (CP) and lysine (LYS) on characteristics of performance, egg internal quality, and nitrogen balance/retention. It was used 160 Hisex White laying hens at 48 weeks of age, individually accomodated in a complete random design in a 4 × 2 factorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 13 publications
7
9
3
5
Order By: Relevance
“…These findings are consistent with those reported by Silva et al (2010), who evaluated diets with different crude protein levels (12, 14, 16, and 18%) supplemented with synthetic amino acids and observed that feed intake, egg weight, egg mass, and albumen percentage linearly increased with increasing crude protein levels. On the other hand, when evaluating crude protein level reduction from 16.5 to 15.25% with no amino acid supplementation in 24-wk-old Lohmann layer diets, did not find any differences in feed intake or feed conversion ratio per egg mass or per dozen eggs.…”
Section: High-fiber Diets With Reduced Crude Protein For Commercial Lsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with those reported by Silva et al (2010), who evaluated diets with different crude protein levels (12, 14, 16, and 18%) supplemented with synthetic amino acids and observed that feed intake, egg weight, egg mass, and albumen percentage linearly increased with increasing crude protein levels. On the other hand, when evaluating crude protein level reduction from 16.5 to 15.25% with no amino acid supplementation in 24-wk-old Lohmann layer diets, did not find any differences in feed intake or feed conversion ratio per egg mass or per dozen eggs.…”
Section: High-fiber Diets With Reduced Crude Protein For Commercial Lsupporting
confidence: 92%
“…On the other hand, low crude protein levels determine low nitrogen availability, and therefore, better nitrogen utilization. Silva et al (2010), studying the effect of different crude protein levels (12, 14, 16, or 18%) on the nitrogen balance of Hisex White 49-wk-old layers, observed a positive linear effect on nitrogen intake and excretion. The utilization of fecal nitrogen exceeded 50% only when the 12% crude protein diet was fed.…”
Section: High-fiber Diets With Reduced Crude Protein For Commercial Lmentioning
confidence: 99%
“…In contrary to this Silva et al (2010) observed nonsignificant response on EW and EM by various concentrations of lysine in diet. In current study indicating that CP had no effect on EW and EM.…”
Section: Egg Weight (Ew) and Egg Mass (Em)contrasting
confidence: 76%
“…Contrariando os resultados verificados neste estudo, Schutte & Smink (1998) constataram que a ingestão de lisina total não diferiu entre poedeiras alimentadas com rações com 16,4% PB e suplementadas com 0,04; 0,08; 0,12; 0,16; 0,20; 0,24 e 0,28% de lisina total. Silva et al (2010), com 12; 14; 16 e 18% de proteína e 0,85 e 1,00% de lisina total, também não observaram diferenças no consumo de lisina e proteína. Já Prochaska et al (1996) e Goulart (1997) observaram maior consumo de lisina com o aumento do nível de lisina das dietas de poedeiras comerciais, como registrado neste estudo (Tabela 5).…”
Section: Resultsunclassified
“…Em poedeiras com 32 semanas de idade, Jardim Filho et al (2010) verificaram que as maiores retenções de nitrogênio foram obtidas com fornecimento de 700 a 800 mg de lisina digestível/kg de ração e permitiram os melhores valores de balanço de nitrogênio e a maior quantidade de nitrogênio retido por grama de massa de ovo depositada. Silva et al (2010), no entanto, não verificaram efeito dos níveis de proteína e de lisina no balanço de nitrogênio em poedeiras com 48 semanas de idade.…”
Section: Introductionunclassified